Hydrothermal Catalytic Conversion of Glucose into Lactic Acid with Acidic MIL-101(Fe) - Xiaofang Liu; Zhigang Liu; Qiuyun Zhang; Hongguo Wu; Rui Wang (Journal of Chemistry)
MIL-101(Fe) was explored for the first time for the catalytic conversion of glucose into lactic acid (LA). The as-synthesized MIL-101(Fe) was successfully characterized, and its higher specific surface area, porosity, and feasible acid properties were confirmed to determine the remarkable catalytic activity in glucose-to-LA conversion (up to 25.4% yield) compared with other catalysts like MIL-101(Cr, Al) and UiO-66(Zr). The reaction parameters including temperature, reaction time, and substrate species as well as catalyst reusability were discussed.